2021
DOI: 10.1002/anie.202016802
|View full text |Cite
|
Sign up to set email alerts
|

A Palette of Minimally Tagged Sucrose Analogues for Real‐Time Raman Imaging of Intracellular Plant Metabolism

Abstract: Sucrose is the main saccharide used for longdistance transport in plants and plays an essential role in energy metabolism; however, there are no analogues for real-time imaging in live cells. We have optimised a synthetic approach to prepare sucrose analogues including very small (% 50 Da or less) Raman tags in the fructose moiety. Spectroscopic analysis identified the alkyne-tagged compound 6 as a sucrose analogue recognised by endogenous transporters in live cells and with higher Raman intensity than other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 93 publications
0
24
0
Order By: Relevance
“…Reproduced with permission. [75] Copyright 2021 Wiley-VCH. E) Three-color multiplex imaging of EU- 13 C 2 (RNA), EdU-13 C (DNA) and 17-ODYA (fatty acids) using an alkyne isotopic editing strategy.…”
Section: Miniaturized Raman Labels For Metabolic Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [75] Copyright 2021 Wiley-VCH. E) Three-color multiplex imaging of EU- 13 C 2 (RNA), EdU-13 C (DNA) and 17-ODYA (fatty acids) using an alkyne isotopic editing strategy.…”
Section: Miniaturized Raman Labels For Metabolic Imagingmentioning
confidence: 99%
“… [74] Our group synthesized a collection of sucrose analogues, from which aminopropargyl sucrose was used for trafficking studies in live plant cells for the first time (Figure 5). [75] Furthermore, SRS microscopy of sialylated glycans using a similar tagging strategy has been reported [76] . In addition to alkynes, nitrile and isonitrile groups have also been employed as small Raman tags for metabolite detection, such as rhabduscin in bacteria [77] and the small molecule drug, neratinib [78] .…”
Section: Miniaturized Raman Labels For Metabolic Imagingmentioning
confidence: 99%
“…For example, de Moliner et al reported real-time visualization of sucrose uptake in plant cells using an alkyne-tagged sucrose. 108 Coronatine, a bacterial virulence factor, resembles a plant hormone and can thus hijack the plant system. 109 Unfortunately, fluorescence-labelled coronatine loses its activity, but alkyne modification does not affect the activity.…”
Section: Atri Of Biomolecules and Bioactive Mimicsmentioning
confidence: 99%
“…For example, de Moliner et al reported real-time visualization of sucrose uptake in plant cells using an alkyne-tagged sucrose. 108 …”
Section: Alkyne Tag Raman Imagingmentioning
confidence: 99%
“…It is worth mentioning that AuNPs are excellent substrates for surface-enhanced Raman spectroscopy (SERS), which is widely utilized for the precise monitoring of therapeutic progression through Raman fingerprints at the molecular level. SERS attributes clear-cut molecular evidence that improves the selectivity, accuracy, and specificity of multiplex detection by avoiding spectral overlap, making it a reliable tool for molecular diagnostics . The high intensity signature Raman peaks from the SERS tags can provide in depth information regarding intercellular distribution. Even though a number of Raman reporter molecules are well-known with excellent Raman cross-section, the problem associated with photobleaching remains as a bottleneck .…”
Section: Introductionmentioning
confidence: 99%